Digital Transformation through Integrated Business Excellence: An Empirical Investigation of Auto Component Industries in Chennai's Manufacturing Ecosystem - J, Eugene; R, Dr. Arivazhagan; Dutta , Dr. Surjadeep (International Journal of Accounting and Economics Studies, 2025)
Purpose – This research develops and validates an integrated business excellence model that connects traditional operational excellence and digital innovation capabilities in the auto component manufacturing industry in Chennai. The research fills the gap in the literature around managing the divide between initiatives to pursue digital transformation and the ability of the organization to sustain strong business performance, considering the context of an emerging economy.Design/methodology/approach – A mixed-methods empirical approach was undertaken.  The research surveyed 247 auto component manufacturers in Chennai using structured questionnaires and also conducted in-depth interviews with 28 senior executives. The integrations of business excellence framework was validated (along with the key variables/topics) using square equation modelling/structures Equation modeling (SEM) and factor analysis.Findings – The integrated model identifies five key dimensions: Digital Process Excellence (DPE), Innovation Management Capability (IMC), Quality Systems Integration (QSI), Supply Chain Digitalization (SCD), and Performance Measurement Systems (PMS). The model shows robust, significant positive relationships between digital innovation alignment and business excellence, with Quality Systems Integration as the most robust mediator (β = 0.743, p < 0.001).Originality/value – In order to facilitate digital transformation while preserving operational excellence, this research has developed and experimentally tested a framework tailored to the automotive component industries in developing markets.
Keywords: Digital transformation, Business excellence, Auto components, Manufacturing, Chennai, Industry 4.0